Skeletal Muscle, but not Cardiovascular Function, Is Altered in a Mouse Model of Autosomal Recessive Hypophosphatemic Rickets - Wacker, Michael J.; Touchberry, Chad D.; Silswal, Neerupma; Brotto, Leticia; Elmore, Chris J.; Bonewald, Lynda F.; Andresen, Jon; Brotto, Marco (Frontiers in Physiology, 2016)
Autosomal recessive hypophosphatemic rickets (ARHR) is a heritable disorder characterized by hypophosphatemia, osteomalacia, and poor bone development. ARHR results from inactivating mutations in the DMP1 gene with the human phenotype being recapitulated in the Dmp1 null mouse model which displays elevated plasma fibroblast growth factor 23. While the bone phenotype has been well characterized, it is not known what effects ARHR may also have on skeletal, cardiac, or vascular smooth muscle function, which is critical to understand to treat patients suffering from this condition. In this study, the extensor digitorum longus (EDL- fast-twitch muscle), soleus (SOL- slow-twitch muscle), heart, and aorta were removed from Dmp1 null mice and ex-vivo functional tests were simultaneously performed in collaboration by three different laboratories. Dmp1 null EDL and SOL muscles produced less force than wildtype muscles after normalization for physiological cross sectional area of the muscles. Both EDL and SOL muscles from Dmp1 null mice also produced less force after the addition of caffeine (which releases calcium from the sarcoplasmic reticulum) which may indicate problems in excitation contraction coupling in these mice. While the body weights of the Dmp1 null were smaller than wildtype, the heart weight to body weight ratio was higher. However, there were no differences in pathological hypertrophic gene expression compared to wildtype and maximal force of contraction was not different indicating that there may not be cardiac pathology under the tested conditions. We did observe a decrease in the rate of force development generated by cardiac muscle in the Dmp1 null which may be related to some of the deficits observed in skeletal muscle. There were no differences observed in aortic contractions induced by PGF2a or 5-HT or in endothelium-mediated acetylcholine-induced relaxations or endothelium-independent sodium nitroprusside-induced relaxations. In summary, these results indicate that there are deficiencies in both fast twitch and slow twitch muscle fiber type contractions in this model of ARHR, while there was less of a phenotype observed in cardiac muscle, and no differences observed in aortic function. These results may help explain skeletal muscle weakness reported by some patients with osteomalacia and need to be further investigated.